PEMBERDAYAAN IBU-IBU PKK MELALUI PELATIHAN DAN PENDAMPINGAN PRODUKSI SABUN DAN DETERJEN - Elfi Susanti VH; Endang Susilowati (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2016)
Improvement of social welfare can be done with a variety of approaches, by empowering the community. Empowering ibu-ibu PKK RT 03 and RT 04 in Joho Mojolaban through training and mentoring the production of soaps and detergents. This activity is done in order to enhance the dignity of society who are in a state of not being able to rely on his own strength. Objectives and specific targets to be achieved in this activity is ibu-ibu PKK RT 03 and RT 04 interested and motivated to entrepreneurship, formed group of PKK members who become economically independent by producing soaps and detergents, as well as realize the PKK RT 03 and RT 04 more powerful, more productive, creative, and responsive. To achieve these objectives, the team of Chemical Education FKIP UNS has provided counseling, training and assistance ibu-ibu PKK in producing soaps and detergents. Ibu-ibu PKK is given knowledge about entrepreneurs and home-based business opportunities, as well as basic principles of production. Ibu-ibu PKK were also given training on how to make soap and detergents, as well as product packaging and marketing techniques.Keywords: soaps, detergents, counseling, training, production